THE PROBLEM OF NORMALIZATION AND CODIFICATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
One of the most important tasks of linguistics in defining the problem of literary language is the study of the range of general issues subject to consideration and definition in the normalization and codification of the norm of linguistic units of a specific language, and its in-depth study using the example of each literary language. In this article, for the first time, an attempt has been made to provide brief information on some issues related to the normalization of the Kyrgyz literary language and its codification.
Keywords: Kyrgyz language, national literary language, standardization, codification, language norm, style, grammar